Kakadu Conservation Zone Inquiry : summary - Australia. Resource Assessment Commission; Stewart, Donald Gerard; Kakadu Conservation Zone Inquiry (Australia) (Canberra : Aust. Govt. Pub. Ser., 1991)
Summary of principal findings, conclusions and recommendations on the options available for the use of resources of the Kakadu Conservation Zone; implications for the national economy and the Jawoyn people.
"May 1991"
Cover title: Kakadu Conservation Zone Inquiry final report summary.
Commission headed by Mr Justice Stewart.
"A summary of the final report of the Resource Assessment Commission's Inquiry into options for the uses of the resources of the Kakadu Conservation Zone." --Pref.
Keywords: Kakadu Conservation Zone Inquiry (Australia); Aboriginal Australians -- Northern Territory -- Kakadu National Park -- Mines and mining; Conservation of natural resources -- Northern Territory -- Kakadu National Park; Mineral industries -- Environmental aspects -- Northern Territory -- Kakadu National Park; Kakadu Conservation Zone; Jawoyn people (N57) (NT SD53-09); Mining industry; Kakadu National Park (N.T.); Kakadu Region (N.T.); Kakadu / Alligator Rivers area (NT SD53-01, SD53-05)